COMMUNITY STRUCTURE of EPIZOIC DIATOM Pinna muricata AT SEAGRASS ECOSISTEM IN PANDARATAN BEACH TAPANULI TENGAH REGENCY NORTH SUMATRA PROVINCE - Dalimunthe, Salmi Patima; Samiaji, Joko; Siregar, Sofyan Husein (Asian Journal of Aquatic Sciences, 2023)
This research was carried out in March 2022; the location of this research is Pandaratan Beach, Tapanuli Tengah Regency, North Sumatra Province. The purpose of this study was to determine the abundance, relative abundance, diversity index, dominance index, and uniformity index of epizoic diatom species in Pinna muricata in the seagrass ecosystem of Pandaratan Beach. The method used is a survey method, using three sampling points to take p.muricata, the determination of 3 sampling points based on the density of the seagrass ecosystem. Sampling of diatoms was carried out by scraping the surface of the shells 5 cm wide, on the right and left backs of the shells. The diatom samples obtained were then analyzed in the laboratory. There were 12 types of epizoic diatoms found, consisting of Amphora sp, Bacillaria sp, Cyclotella sp, Cymbella sp, Isthmia sp, Melosira sp, Navicula sp, Nitzschia sp, Pinnularia sp, Skeletonema sp, Surirella sp, Synedra sp. the average value of epizoic diatom abundance on the shells of Pinna muricata ranged from 2.711,28–4.617,84 ind/cm2, the average value of the diversity index (H') of epizoic diatoms ranged from 1.43-2.50. The mean value of the dominance index (D) is in the range of 0.26 to 0.92. The average value of the uniformity index (E) ranges from 0.40-0.70.